2021
DOI: 10.21203/rs.3.rs-542843/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Hypoxia adipose stem cell-derived exosomes promote high-quality healing of diabetic wound involves activation of PI3K/Akt pathways

Abstract: Refractory diabetic wounds can cause persistent inflammation and delayed healing due to hypoxia. Currently, no optimal solution is available. Exosomes of adipose stem cells (ADSCs-exo) may promote skin wound healing, however, molecular mechanisms remains mysterious. We found significantly enhanced survival and proliferation of adipose stem cells after hypoxia induction compared to normoxia. Here, we aimed to investigate if hypoxic adipose stem cells exosomes (HypADSCs-exo) participate in hypoxia adaptability a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…This could be a consequence of the stemnessmaintaining effects of hypoxia. Recent studies have shown that hypoxia can stimulate the proliferation of dermal papilla cells [23] , dental pulp stem cells [24] , neural stem cells [25] , and mesenchymal stem cells [26] , among others [27][28][29] . To some extent, dermal papilla cells can be considered a unique source of mesenchymal stem cells [30] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This could be a consequence of the stemnessmaintaining effects of hypoxia. Recent studies have shown that hypoxia can stimulate the proliferation of dermal papilla cells [23] , dental pulp stem cells [24] , neural stem cells [25] , and mesenchymal stem cells [26] , among others [27][28][29] . To some extent, dermal papilla cells can be considered a unique source of mesenchymal stem cells [30] .…”
Section: Discussionmentioning
confidence: 99%
“…As this self-renewal process significantly enlarges stem cell pools, the proliferation-promoting effect of hypoxia could increase tissue density rather than tissue volume. Specifically, our results showed that hypoxia decreased the PAX6-and CHX10-positive RPCs ratio [22][23][24][25][26][27][28][29][30][31][32][33][34] . A previous study using the adherent differentiation method to generate RPCs showed that a low-oxygen environment could increase the percentage of RPCs co-expressing PAX6 and CHX10 [35] .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, considerable interest has been elicited in the clinical application of exosomes. Numerous studies have recently shown the therapeutic role of MSC-derived exosomes to regenerate skin and enhance various renal, cardiovascular, and liver injuries [12][13][14], as well as have therapeutic potential in skin anti-aging. However, low yield, difficult preparation, and harsh transportation and storage conditions lead to the partial degradation of active components in exosomes and thus decline their anti-aging ability to limit the wide application of exosomes [15].…”
Section: Introductionmentioning
confidence: 99%
“…To date, the role and therapeutic potential of stem cell-derived sEV in cartilage repair and regeneration have attracted considerable attention worldwide [ 13 ]. Recently, some studies revealed that sEV derived from adipose tissue-derived mesenchymal stem cells (ADMSCs) promoted repair and regeneration of damaged tissues, alleviated degradation of aged organs, and maintained the homeostasis of the body [ 14 17 ]. In OA treatment, several studies indicated that MSCs-derived sEV (MSCs-sEV) significantly promoted chondrocyte proliferation in vitro and in vivo [ 18 21 ].…”
Section: Introductionmentioning
confidence: 99%